2021
DOI: 10.1088/1361-6560/ac1246
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in beam’s eye view fiducial tracking using a novel multilayer imager

Abstract: Purpose. Electronic portal image devices (EPIDs) have been investigated previously for beams-eye view (BEV) applications such as tumor tracking but are limited by low contrast-to-noise ratio and detective quantum efficiency. A novel multilayer imager (MLI), consisting of four stacked flat-panels was used to measure improvements in fiducial tracking during liver stereotactic body radiation therapy (SBRT) procedures compared to a single layer EPID. Methods. The prototype MLI was installed on a clinical TrueBeam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The flat-panel imager used in the present study employs a multilayer architecture, vertically stacking four identical detection layers each analogous to current commercially available EPIDs. This multilayer imager (MLI) was found to increase performance metrics such as DQE and contrast-tonoise ratio (CNR) over single layer imagers (Harris et al 2020), while also conferring improvement to clinical EPID applications such as beam's-eye-view tumor tracking (Harris et al 2021). Furthermore, the MLI may provide better quality images at lower doses (Hu et al 2018, Myronakis et al 2020, and the layering can be used for spectral imaging (Myronakis et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The flat-panel imager used in the present study employs a multilayer architecture, vertically stacking four identical detection layers each analogous to current commercially available EPIDs. This multilayer imager (MLI) was found to increase performance metrics such as DQE and contrast-tonoise ratio (CNR) over single layer imagers (Harris et al 2020), while also conferring improvement to clinical EPID applications such as beam's-eye-view tumor tracking (Harris et al 2021). Furthermore, the MLI may provide better quality images at lower doses (Hu et al 2018, Myronakis et al 2020, and the layering can be used for spectral imaging (Myronakis et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of promising techniques are being explored, including multi-layered scintillators, novel scintillating materials, and direct conversion detectors 43 47 New EPIDs have been developed with measured DQE(0) of 6.7%, 44 8.0%, 45 9.7%, 46 and 22% 43 . One application of that research demonstrated that single-energy MV CT images acquired with a four-layer EPID have superior image quality relative to MV and kV images acquired with a single-layer detector in the presence of titanium and aluminum implants 48 .…”
Section: Discussionmentioning
confidence: 99%
“…This improved the robustness and transferrability of the model between institutions. Furthermore, recent research has been dedicated towards the improvement of detective quantum efficiency and contrast-tonoise ratio of the MV imager, which include the multi-layer imager (MLI) design (Myronakis et al 2017, Hu et al 2018, Harris et al 2020, 2021, pixelated scintillation (Star-Lack et al 2015) and advanced scintillation materials (Hu et al 2019). Harris et al (2021) demonstrated a 41.7% increase in marker tracking efficiency (number of frames that successfully track markers compared to maximum number of trackable frames) when using a novel multilayer MV imager.…”
Section: Discussionmentioning
confidence: 99%